KONTRIBUSI PEREMPUAN PEKERJA DALAM KELUARGA DI PERKOTAAN: KONTRIBUSI PEREMPUAN PEKERJA DALAM KELUARGA DI PERKOTAAN - Mirna Taufik (ECO-BUILD, 2019)
In the current era of global competition, women and the world of work are not a taboo subject to be discussed. Nowadays women workers have increased increasingly high of course this is supported by the existence of gender equality. where there are equal work rights between men and women. In fact, women are often the main workers in the family. increasing needs in the family require women to become workers to help fulfill the family's economy. therefore, this study aims to explore the contribution of women workers in the family, especially informal sector workers in the city of Palembang. The method used in this study is a qualitative method by collecting data through surveys, interviews, and also observations. Data analysis was performed using data reduction, data display and drawing conclusions. The results of the study found that the contribution of women workers in urban families, namely women, not only work to take care of the house, husband and children, but women also had towork outside the home and make money to help build the family economy. of course the motivation or desire of working women is driven by the increasing family needs of the day, low husband's income and even sometimes there are husbands who do not work .of course as a woman working as well as a wife and mother is not an easy thing but for the family economy women workers have to divide their time between working outside the home and inside the house so that all the goals can be achieved .